Tariffs under Globalization 3.0 - Frank T. Lorne; Xiyi Yang (Journal of Management Practices, Humanities and Social Sciences, 2019)
The aim of this study is to examine the role that tariffs could possibly play beyond an infant industry argument, by considering three scenarios on how a technological competition can evolve, an approach that is built on the principle of fairness. At Davos, World Economic Forum (2019) characterized globalization as evolving from the old silk road (Globalization 1.0) to now possibly entering a phase of Globalization 4.0. The possibility of the new phase of globalization is partially triggered by a de-globalization movement grounded on populist sentiment and a promotion of “me-first” rather than a “win-win”, moving away from the neoclassical framework of international trade based on the balance of current account and capital account, the principle by which Globalization 3.0 has operated for many years. Some country leaders blatantly ignored standard textbook framework on international trade, advocating fair trade principle based on zero current account balance as the ideal. The threat of raising tariffs as a policy tool can escalate into an excuse for a revival of Keynesian economics applied globally, resulting in “lose-lose” rather than “win-win” outcome that neoclassical economics advocates. Can tariffs be rationalized beyond an attempt to pursue Keynesian economics? With a game-theoretical perspective heuristically explained in a neoclassical framework of international trade, this study further evaluates the possible consequences of tariffs under Globalization 3.0 and speculate on its effectiveness in promoting new concepts for Globalization 4.0. This study advocates that if a neoclassical approach to international trade will ever be revisited, an appropriate framework for discussing future policy must be used. It concludes that tariffs are ineffective in helping to facilitate the rules of a game that can determine the winner of a technological race under a Rawlsian veil of ignorance, which is not the whole part but nevertheless an important aspect of globalization 4.0.